Ferroptosis and Its Role in Epilepsy - Cai, Yuxiang; Yang, Zhiquan (Frontiers in Cellular Neuroscience, 2021)
Epilepsy is one of the most common symptoms of many neurological disorders. The typical excessive, synchronous and aberrant firing of neurons originated from different cerebral cortex cause spontaneous recurrent epileptic seizures. Up to one-third of epileptic patients belong to drug-resistant epilepsy. Prolonged epilepsy can lead to neuronal damage and cell death. The mechanisms of epileptic pathogenesis and neuron death are not clear. Ferroptosis is a newly defined form of regulated cell death, which is characterized by the overload of intracellular iron ions, leading to the accumulation of lethal lipid-based reactive oxygen species. Previous studies mainly focus on its role in tumor and various neurological disorders including epilepsy. Current researches show that inhibition of ferroptosis is likely to be an effective therapeutic approach for epilepsy. In this review, we outline the pathogenesis of ferroptosis, regulatory mechanisms of ferroptosis, related regulatory molecules targeting ferroptosis and their effects in epilepsy. Providing a new direction for discovering new therapeutic targets on epilepsy.